Plant Responses to Abiotic Stress Regulated by Histone Deacetylases - Luo, Ming; Cheng, Kai; Xu, Yingchao; Yang, Songguang; Wu, Keqiang (Frontiers in Plant Science, 2017)
In eukaryotic cells, histone acetylation and deacetylation play an important role in the regulation of gene expression. Histone acetylation levels are modulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs). Recent studies indicate that HDACs play essential roles in the regulation of gene expression in plant response to environmental stress. In this review, we discussed the recent advance regarding the plant HDACs and their functions in the regulation of abiotic stress responses. The role of HDACs in autophagy was also discussed.